Penegakan Hukum terhadap Pelaku Tindak Pidana Obstruction of Justice dalam Perspektif Hukum Pidana Indonesia - Iqlimah Nadhilah; Ivan Zairani Lisi; Rini Apriyani (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This research aims to analyze criminal acts that may be qualified as perpetrators of the crime of obstruction of justice from the perspective of the criminal law applicable in Indonesia, as well as to analyze the application of the law against perpetrators of obstruction of justice in Indonesia. The type of research used in this thesis is doctrinal research. The doctrinal approach has a normative character; therefore, its object of study consists of a set of legal norms (black letter law) at the level of application (professional constituency), or, at certain levels of analysis, this approach extends to the examination of legal theory. Based on the results of the research, the author finds that the provisions governing acts that may be qualified as the crime of obstruction of justice in Indonesia encompass all forms of interference, from the beginning to the end, with the entire ongoing legal and judicial process. A perpetrator of obstruction of justice is aware that a person has committed a crime or is undergoing a legal process and then deliberately commits acts that may hinder or obstruct law enforcement officials in conducting examinations of the criminal offender, with the purpose that the processes of investigation, prosecution, or examination before the court are impeded, cannot be carried out, or ultimately fail to be carried out. The forms of legal enforcement against perpetrators of acts obstructing the judicial process (obstruction of justice) in Indonesia include, among others, intentionally damaging, concealing, or destroying evidence before or after the commencement of the investigation process.